การศึกษาความเป็นไปได้เบื้องต้นของการลอยแร่โพแทสเซียมเฟลด์สปาร์จากทรายเหลือทิ้ง - นุชรี สองรักษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
The purpose of this research is a pre-feasibility study of separation potassium feldspar from sand waste of the Banpong sand deposit, Banpong district, Ratchaburi Province by using froth flotation and value added from potassium feldspar processing. In order to meet the specification required by the ceramics industry.The study included mineral characterization by using optical microscope, x-ray diffraction, x-ray fluorescence and sieve analysis. High intensity magnetic separator was carried out, in order to decrease the iron contamination and improve quality. The flotation efficiency is evaluated from recovery percentage of potassium feldspar and chemical analysis of floated potassium feldspar by using x-ray fluorescence. The characterization results of sand waste showed that the minerals consisted of feldspar, quartz, muscovite and calcite. The analysis was SiO₂ 84.45 %, K₂O 6.45 %, Na₂O 0.74 %, MgO 0.26%, Fe₂O₃ 1.30 %, TiO₂ 0.24 %, Al₂O₃ 6.15 %, P₂O₅ 0.08 % and CaO 0.23 % respectively. The chemical analysis of floated potassium feldspar of sample -30 mesh as following; SiO₂ 76.87 %, K₂O 11.06 %, Na₂O 1.48 %, MgO 0.08 %, Fe₂O₃ 0.73 %, TiO₂ 0.17 %, Al₂O₃ 8.65 %, P₂O₅ 0.10 % and CaO 0.18 % respectively. The chemical analysis of floated potassium feldspar of sample -60 mesh as following; SiO₂ 76.10 %, K₂O 8.37 %, Na₂O 1.04 %, MgO 0.15 %, Fe₂O₃ 0.95 %, TiO₂ 0.31 %, Al₂O₃ 12.34 %, P₂O₅ 0.12 % and CaO 0.19 % respectively. Economic evaluation from the feldspar processing is also evaluated using the cost and product prices estimation.